2015
DOI: 10.1007/s11250-015-0925-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementation of beef cattle with different protein levels and degradation rates during transition from the dry to rainy season

Abstract: The objective of this study was to evaluate the effect of increasing the supply of protein with different degradation rates on the performance and metabolism of growing Nellore cattle reared on Brachiaria brizantha cv. Marandu pasture during the transition period from the dry to rainy season. The experiment was installed on an area of 34 ha, divided into 12 paddocks with an average area of 2.85 ha. In the performance evaluation were utilized 72 recently weaned, non-castrated Nellore cattle with an initial body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
1
7
0
2
Order By: Relevance
“…According to Ceconi et al (2015), increasing urea nitrogen in dietary supplements during the low peak of ammonia production may improve its use by ruminal bacteria. Fernandes et al (2016) recommended that CP content in the Protein supplements should be only 33% and should come from NPN at the beginning of the dry season. Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Ceconi et al (2015), increasing urea nitrogen in dietary supplements during the low peak of ammonia production may improve its use by ruminal bacteria. Fernandes et al (2016) recommended that CP content in the Protein supplements should be only 33% and should come from NPN at the beginning of the dry season. Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative and qualitative changes occur in tropical pastures during the drought and rainy seasons and in the transition period (Fernandes et al, 2016). These tropical pastures accumulate 77-90% of the total dry matter production (DM) during the rainy season between the months of October and February, comprising high stocking rates in this period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O nível de inclusão de fontes de NNP interfere no consumo voluntário de suplemento. O incremento da participação das fontes de NNP reduz de consumo do suplemento (Fernandes et al, 2016;Tedeschi, Fox & Russell, 2000) e este comportamento fica evidente ao longo do experimento uma vez que, quando houve dife-Tabela III. Peso corporal médio (kg), ganho médio diário (kg/dia) e consumo de suplemento (kg/dia) em bezerros suplementados com diferentes níveis de substituição do farelo de soja por ureia encapsulada (Average body weight (kg), average daily gain (kg/day) and supplement consumption (kg/day) in calves supplemented with different levels of substitution of soybean meal for encapsulated urea).…”
Section: Discussionunclassified
“…Similar study evaluated the effect of different protein concentrations on performance and metabolism of Nellore cattle in tropical pasture during the transition period from dry season to the rainy season [23]. The results showed that the response to supplementation is related to forage plant characteristics (e.g., forage canopy), resulting in benefits only at the early stage of the transition period from dry to rainy season.…”
Section: Nutrientsmentioning
confidence: 99%